2005
DOI: 10.1287/opre.1050.0222
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Aggregation of Set-Partitioning Constraints in Column Generation

Abstract: Column generation is often used to solve problems involving set-partitioning constraints, such as vehicle-routing and crew-scheduling problems. When these constraints are in large numbers and the columns have on average more than 8-12 nonzero elements, column generation often becomes inefficient because solving the master problem requires very long solution times at each iteration due to high degeneracy. To overcome this difficulty, we introduce a dynamic constraint aggregation method that reduces the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…Then, the value of the dual variables are no meaningful measure for which column to adjoin to the RMP. As a remedy, Elhallaoui et al (2003) propose a dynamic row aggregation technique. Their intuition is that in applications like vehicle routing and crew scheduling, some activity sequences are more likely to occur than others: In airline crew scheduling a pilot usually stays in the aircraft with which he starts his duty day.…”
Section: Row Aggregation For Set Partitioning Problemsmentioning
confidence: 99%
“…Then, the value of the dual variables are no meaningful measure for which column to adjoin to the RMP. As a remedy, Elhallaoui et al (2003) propose a dynamic row aggregation technique. Their intuition is that in applications like vehicle routing and crew scheduling, some activity sequences are more likely to occur than others: In airline crew scheduling a pilot usually stays in the aircraft with which he starts his duty day.…”
Section: Row Aggregation For Set Partitioning Problemsmentioning
confidence: 99%
“…Due to the possibility of excluding favorable columns depending on the choice of aggregation, the aggregation is dynamically updated if one detects incompatible columns that have a favorable reduced cost. A theoretical framework for this methodology was first proposed by Villeneuve [1999], while the first implementation of dynamic constraint aggregation can be found in Elhallaoui et al [2005]. Elhallaoui et al [2010] make the procedure so-called multi phase.…”
Section: Dynamic Constraint Aggregationmentioning
confidence: 99%
“…According to Elhallaoui et al [2005], the initial motivation for constraint aggregation arose in crew scheduling applications, where it was observed that crews very rarely change vehicles. A similar property is also true for the PAS problem: here the transferring of patients is extremely undesirable.…”
Section: Dynamic Constraint Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…Carvalho (2005) derives a family of valid dual cuts that can accelerate CG and applies this method in the context of the cutting-stock problem. Elhallaoui et al (2005) suggest a dynamic constraint aggregation method that reduces the number of set-partitioning constraints and present results in the context of urban mass-transit scheduling. Amor et al (2006) attempt to generate deep dual-optimal cuts for improving the effectiveness of their CG procedure, and test this approach on the cutting-stock problem.…”
Section: Motivation For Our Studymentioning
confidence: 99%